エンダービーランド リーセル・ラルセンサン チイキ ノ チガク チョウサ ホウコク 2000-2001 (JARE-42) - 船木, 實; フナキ, ミノル; 石川, 尚人; イシカワ, ナオト; 山崎, 明; ヤマザキ, アキラ; 松田, 高明; マツダ, タカアキ; Dolinsky, Peter; Funaki, Minoru; Ishikawa, Naoto; Yamazaki, Akira; et al. (2003)
P(論文) 第42次南極地域観測隊(JARE-42)夏隊の5名は、2000年12月18日から2001年2月18日まで、南極、エンダービーランド、アムンゼン湾内にあるリーセル・ラルセン山周辺で古地磁気学と岩石年代学の岩石試料採集、磁場探査、及び電磁探査を行った。調査にあたり、第38次隊がリチャードソン湖東岸に建設した発電棟の側に新たに居住棟を建設しリーセル・ラルセン山キャンプとした。古地磁気学調査では86地点から741試料を採集した他、帯磁率の測定や磁鉄鉱-石英片麻岩の分布も調べた。岩石年代学では珪長質片麻岩と塩基性貫入岩試料を187試料採集した。MT法による電磁探査はモレーン上の5地点とリチャードソン湖上の1地点で行い、深さ8kmから28kmで電気比抵抗が小さくなる構造を明らかにした。磁場探査は7000nTに及ぶ磁気異常が片麻岩、あるいは貫入岩の走向と平行に発達している様子を明らかにした。 63日の滞在期間中、最大瞬間風速は50.7m/sを記録したこともあったが、比較的天候に恵まれ、また、設営面での大きな事故も無く順調にキャンプの運営ができた。調査終了後、環境保全の観点から、リーセル・ラルセン山キャンプ設備をすべて撤収した他、50km西方にあるトナー島キャンプ設備も全て撤収した。 Five members of the summer party of the 42nd Japanese Antarctic Research Expedition (JARE-42) stayed in the Mt. Riiser-Larsen area, Amundsen Bay, Enderby Land, Antarctica, from December 18, 2000 to February 18, 2001 for paleomagnetism, geochronology, electromagnetic and magnetic surveys. A resident hut was built beside the generator hut constructed by JARE-38 in the camp. For the paleomagnetic study, 741 samples from 86 sites were collected in addition to the data of susceptibility and distribution of magnetite-quartz gneiss. 187 samples of felsic gneisses and basic dike rocks were collected for the geochronology. The high conductivity layer between 8 and 28 km was elucidated by the magnetotelluric method applied to samples obtained from 5 sites on the moraine field and 1 site on Richardson Lake. Strong magnetic anomalies up to 7000 nT were observed along gneissosity and dike intrusions by the magnetic survey. The weather was relatively mild during 63 days, although the maximum wind speed reached 50.7m/s. The camp was maintained without major accidents or trouble. After the work was completed, the camp facilities at Mt. Riiser-Larsen and Tonagh Island were completely withdrawn for environmental protection. departmental bulletin paper